PERANCANGAN ANIMATED MUSIC VIDEO UNTUK LAGU KELAPA MUDA BAND - Yesaya Sabda Imanuel; Ahmad Khoirul Anwar; Yudi Wibowo (Akademi Seni dan Desain Indonesia Surakarta, 2024)
Kelapa Muda Band is an experimental jazz music group originating from Lampung, Indonesia, and has won the first championship in one of the international jazz music competitions. However, the Kelapa Muda Band is still rarely recognized by the general public who are not concerned with the jazz music genre. One problem is the lack of promotional media for music video clips. Therefore, promotional media for music video clips is needed to increase the name of the Kelapa Muda Band, especially the song